Memory bias in the temporal bisection point - Levy, Joshua M.; Namboodiri, Vijay M. K.; Hussain Shuler, Marshall G. (Frontiers in Integrative Neuroscience, 2015)
The ability to time intervals confers organisms, including humans, with many remarkable capabilities. A common method for studying interval timing is classification, in which a subject must indicate whether a given sample interval is nearer a previously learned short or long reference interval. This task is designed to reveal the sample interval that is equally likely to be labeled as short or long, known as the temporal bisection point. Studies have found that this bisection point is influenced by a variety of factors including the ratio of the target intervals, the spacing of the sample intervals, the modalities of the stimuli, the attentional load, and the inter-trial duration. While several of these factors are thought to be mediated by memory effects, the prototypical classification task affords no opportunity to measure these effects directly. Here, we present a novel bisection task, termed the “Bisection by Classification and Production” (BiCaP) task, in which classification trials are interleaved with trials in which subjects must produce either the short or long referents or their midpoint. Using this method, we found a significant correlation between the means of the remembered referents and the bisection points for both classification and production trials. We then cross-validated the bisection points for production and classification trials by showing that they were not statistically differentiable. In addition to these population-level effects, we found within subjects evidence for co-variation across a session between the production bisection points and the means of the remembered referents. Finally, by using two sets of referent durations, we showed that only bias-corrected measures were consistent with a previously reported effect in which the ratio of the referents affects the location of the bisection point. These results argue that memory effects should be considered in temporal tasks.